Are they still determining? Analysis of associations among ethnicity, gender, socioeconomic status, neighborhood factors, and COVID-19 vaccination - Kim, Bokyung; Hong, Seoyeon; Kim, Sungwook (Frontiers in Communication, 2023)
Introduction This study explores associations among adult vaccination, ethnicity, gender, and socioeconomic variables such as educational attainment and income, as well as neighborhood factors. Methods A telephone quota sample of New Jersey adults (N = 1,984) was used to text associations among proposed predictors of vaccination behaviors. Results Our multivariate logistic regression analyses found that certain races/ethnicity, respondents' household income, and perceived safety of one's community were the strongest predictors of COVID-19 vaccination. The odds of COVID-19 vaccination were 52% lower for Black/African American respondents compared to white/Caucasian respondents (p = 0.001) and 44% lower for Hispanic/Latino respondents compared to white/Caucasian respondents (p = 0.001). Discussion The results add new insights to public health communication research and suggest careful interventions across racial groups, considering existing racial disparities in vaccination.